Heterogeneity in Alzheimer's disease: progression rate segregated by distinct neuropsychological and cerebral metabolic profiles. - Mann, U M (1992)
In an attempt to define possible subgroups of Alzheimer's disease, 21 patients satisfying current clinical diagnostic criteria for this disorder were divided on the basis of progression rates of symptoms. Thirteen patients with relatively rapid intellectual deterioration did not differ from eight patients showing slow progression with respect to global intellectual performance, sex, or age at onset of symptoms. Neuropsychological testing revealed that although the two groups were indistinguishable in verbal or visuospatial functions associated with the parietotemporal cortex, the more rapidly deteriorating group had significantly greater impairment in executive functions attributed to the frontal lobe. PET scans showed equivalent reductions in glucose metabolism in the parietotemporal cortex, but patients with relatively fast progression had significantly greater hypometabolism frontally. These results suggest an association between relatively severe frontal lobe involvement and a rapid clinical course that might have important implications for the development of treatment strategies for patients with Alzheimer's disease.